STUDI LITERATUR : PENERAPAN AKUPRESUR TERHADAP INTENSITAS NYERI PERSALINAN KALA I - I Gusti Ayu Agung Sartika; Gusti Ayu Marhaeni; Ni Gusti Kompiang Sriasih (Forind Press, 2026)
Labor pain is a physiological condition experienced by almost all women during childbirth. Managing labor pain is a fundamental goal of intrapartum care, and non-pharmacological approaches-such as acupressure-are utilized for this purpose. Acupressure is a simple, side-effect-free, non-pharmacological method that can serve as an alternative for reducing labor pain. Research Objective: To determine the effect of acupressure on reducing the intensity of labor pain during the first stage of labor. This study employed a literature review method; the article selection process followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, comprising four stages: identification, screening, eligibility assessment, and inclusion. Articles were obtained by searching the Google Scholar database using a combination of keywords: acupressure, pain, and first-stage labor. Subsequently, duplicate articles were removed, screening was conducted based on titles and abstracts, and eligibility was assessed through full-text review. Articles meeting the inclusion criteria were then evaluated for methodological quality using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist. Articles that passed the quality assessment were included in the final synthesis to analyze the effect of acupressure techniques on reducing labor pain intensity during the first stage of labor. Based on the literature review results, it can be concluded that acupressure techniques are effective in reducing the intensity of labor pain during the first stage of labor.